EFEKTIVITAS DAN HAMBATAN PEMANFAATAN LABORATORIUM DALAM MENDUKUNG PEMBELAJARAN IPA DI SMP NEGERI 14 PEKANBARU TAHUN AJARAN 2017/2018 - Indo Siti Nurul Aini; Darmawati Darmawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Research has been carried out at Pekanbaru SMP 14 in September to December 2018 which aims to determine the effectiveness and constraints on the use of laboratories in supporting science learning in Pekanbaru Public Middle School 2017/2018 academic year. The sample in this study were science teachers as many as 3 science teachers and grade VIII and IX students as many as 234 students. The research instrument used a closed questionnaire, observation sheet, and documentation. Then the data were analyzed descriptively quantitatively. The results showed that the effectiveness of laboratory use in supporting science learning in Pekanbaru State Middle School 14/2014 academic year was 68.45% (quite effective). While the barriers to the use of science laboratories in SMP Negeri 14 Pekanbaru include: the intensity of teachers in participating in laboratory training and the availability of time for practicum activities that are still low and the lack of laboratory facilities that are still lacking. Based on the results of the research it was concluded that the effectiveness of the use of laboratories in supporting science learning in Pekanbaru Public Middle School 2017/2018 academic year was in the category of being quite effective.Keywords: Effectiveness, barriers, laboratories, Science Learning